2010
DOI: 10.2214/ajr.10.4718
|View full text |Cite
|
Sign up to set email alerts
|

MRI Features of Renal Oncocytoma and Chromophobe Renal Cell Carcinoma

Abstract: We have presented the largest series to date of the MRI features of both renal oncocytoma and chromophobe RCC. These related entities exhibited similar findings, and no MRI features were reliable in distinguishing between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(132 citation statements)
references
References 34 publications
2
124
0
6
Order By: Relevance
“…Cystic changes can be observed within a solid tumor, and central necrosis might be absent, even in very large chromophobe carcinomas (50). Signal loss on out of phase images due to microscopic fat has been reported (51). It is interesting that oncocytomas and chromophobe RCC share similar ontogenic and histologic features (on hematoxylin-eosin-stained slides) and some imaging findings.…”
Section: Chromophobe Rccmentioning
confidence: 98%
See 1 more Smart Citation
“…Cystic changes can be observed within a solid tumor, and central necrosis might be absent, even in very large chromophobe carcinomas (50). Signal loss on out of phase images due to microscopic fat has been reported (51). It is interesting that oncocytomas and chromophobe RCC share similar ontogenic and histologic features (on hematoxylin-eosin-stained slides) and some imaging findings.…”
Section: Chromophobe Rccmentioning
confidence: 98%
“…It is interesting that oncocytomas and chromophobe RCC share similar ontogenic and histologic features (on hematoxylin-eosin-stained slides) and some imaging findings. Oncocytomas develop from type B intercalated cells of the cortical collecting duct and are indistinguishable from chromophobe RCC on imaging studies, sharing features such as central scar and spoke wheel pattern of enhancement (51) .…”
Section: Chromophobe Rccmentioning
confidence: 99%
“…Traditional MR imaging features of oncocytoma may be indistinguishable from those of chromophobe RCC (42). However, Zhang et al (39) reported avid enhancement in oncocytomas on contrast-enhanced CT scans but did not find a significant difference between these and clear cell RCCs.…”
Section: Genitourinary Imagingmentioning
confidence: 98%
“…The presence of a central scar was defined as a central stellate area of T2 hyperintensity with lack of enhancement during the nephrographic phase with or without enhancement during subsequent phases [20]. Nonenhancing areas (assessed for only solid tumors) were defined as hypoattenuating, nonenhancing areas which were not sharply demarcated and lacked apparent walls.…”
Section: Assessment Of Imaging Features On Both Ct and Mrimentioning
confidence: 99%